Busulfan administration produces toxic effects on epididymal morphology and inhibits the expression of ZO-1 and vimentin in the mouse epididymis. Issue 6 (12th December 2017) - Fang, Fang; Ni, Ke; Cai, Yiting; Zhao, Qian; Shang, Jin; Zhang, Xiaoke; Shen, Shiliang; Xiong, Chengliang
Abstract : Busulfan is an alkane sulphonate currently used as an anticancer drug and to prepare azoospermic animal models, because it selectively destroys differentiated spermatogonia in the testes. However, few studies have focussed on the exact effects of busulfan treatment on the epididymis currently. The present study assessed the effect of busulfan on epididymal morphology and the blood–epididymis barrier in mice. We treated mice with a single injection of busulfan and detected the effect at different time points. We showed that busulfan was toxic to the morphological structure and function of the epididymis. Furthermore, busulfan treatment down-regulated the epididymal expression of vimentin and zonula occludens-1 (ZO-1) at the mRNA and protein levels. In addition, there was an increase in total androgen receptor (AR) levels, whereas the estrogen receptor-α (ER-α) levels were reduced, both in the caput and cauda regions after busulfan treatment, which may be secondary to the testicular damage. In conclusion, our study describes the effects of busulfan administration on the mouse epididymis and also provides a potential understanding of male infertility arising from chemotherapy-related defects in the epididymis.